1991
DOI: 10.1128/aac.35.10.2020
|View full text |Cite
|
Sign up to set email alerts
|

A DNA sequence upstream of the tet(O) gene is required for full expression of tetracycline resistance

Abstract: The DNA sequences upstream of the tet(O) and tet(M) open reading frames (ORFs) (ca. 300 bp) were found to share a higher degree of homology than those of the tet(O) and tet(M) ORFs themselves. A transcription initiation site for tel(O) was located by primer extension analysis. Campylobacter coli was found to use a promoter sequence different from that used by Escherichia coli. The sequence upstream of tet(O) was shown to be required in cis for high-level resistance to tetracycline.The class 0 tetracycline (TC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…This is consistent with the hypothesis that the tet(M) genes have come from gram-positive bacteria and illustrates the spread of gram-positive genes into gram-negative species (227). This information, along with that of Wang and Taylor (306), is consistent with the hypothesis that tet(O) and tet(S) genes may also be regulated. However, the regulation of tet(Q) expression is unclear since most of the work has been done to determine the regulation of self-transfer and mobilization of both coresident plasmids and unlinked integrated elements, rather than expression of the Tet(Q) protein (152,256,257).…”
Section: Genes Tet(a) Tet(c) Tet(d) Tet(e) Tet(g) and Tet(h)supporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with the hypothesis that the tet(M) genes have come from gram-positive bacteria and illustrates the spread of gram-positive genes into gram-negative species (227). This information, along with that of Wang and Taylor (306), is consistent with the hypothesis that tet(O) and tet(S) genes may also be regulated. However, the regulation of tet(Q) expression is unclear since most of the work has been done to determine the regulation of self-transfer and mobilization of both coresident plasmids and unlinked integrated elements, rather than expression of the Tet(Q) protein (152,256,257).…”
Section: Genes Tet(a) Tet(c) Tet(d) Tet(e) Tet(g) and Tet(h)supporting
confidence: 80%
“…The expression of both Tet(M) and Tet(O) proteins appears to be regulated. Wang and Taylor (306) have suggested that the 400-bp region directly upstream from the coding region of the tet(O) gene was needed for full expression of the gene; however, the function of the region is not understood (292). Burdett (29) reported that the amount of Tet(M) protein increased when streptococci carrying the determinant were exposed to tetracycline.…”
Section: Genes Tet(a) Tet(c) Tet(d) Tet(e) Tet(g) and Tet(h)mentioning
confidence: 99%
“…The upstream region of tet(O) is known to be important for full expression of Tc r (57). To determine if the upstream region of the tet(O) gene played a role in mediating high-level Tc r , the tet(O) gene was cloned from C. jejuni clinical isolate 25-01 (tetracycline MIC ϭ 512 g/ml) incorporating increasing portions of its upstream region into the shuttle vector pRY107 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This organization is characteristic of attenuation terminator sequences (http://www.bork.embl-heidelberg .de/Docu/attenuation/index.html). Similar inverted repeat sequences are located upstream of the ribosome protection genes (24) and tet(M) (21). The expression of tet(M) depends on the synthesis of a 28-amino-acid leader peptide encoded immediately upstream of the tet(M) ribosome binding site (21).…”
Section: ϫ5mentioning
confidence: 99%